(3JLQjO GdbhGYO JLQjO GdYbGFOs - (3eMeO Hf eMeO Hf GdMSf, CHh LYaQ, fUjQ GdOjf GdWhSj , J (B672 (3g` s ((3jhSa ef cHGQ NWGWi GdbQf GdJGSY s)
(3ChdgG (B:s
(3QHfG dG JRZ bdhHfG HYO EP gOjJfG CeG HYO MeO Gddg hGLH GdhLhO Ydi fYeGFg aEfi eLjH Edi eG SFdJ ef JMQjQ eSGFd GdcdGe hJQJjHgG Ydi CHdZ fXGe s
(3BNQgG (B:s
(3hGdENdGd HMce Gddg JYGdi hTQWgeG Yde aGYdgeG HGdhLg hJLhjR GdJCKjQ hGfJaGA GdeaSOI Je GdcJGH hGddg CMeO hGdefI s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B30 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B207s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds